Cimarron Municipal Building Ready for September Opening (Raton, NM Raton Range, 1991)
This article is about the opening of the new Municipal Building in Cimarron New Mexico which will house City Administration, Library, Police Department and Health Clinic.
Newspaper article
Mater List Item # 9
File location is in the New Mexico File Cabinets
Keywords: Iseberg, Raymond Dr; Village of Cimarron; Cimarron Senior Citizens' Center; Municipal Buildings; Building Openings; City Offices; New Bids; Condemned Buildings; Cimarron Park; Cimarron, New Mexico; Ute Park, New Mexico